Polycondensation in liquid crystalline phases of nonionic surfactants. Kinetics and morphology - Kumaraswamy, Guruswamy; Wadekar, M. N.; Agrawal, Vikrant V.; Pasricha, R. (Polymer, 2005)
We have investigated acid-catalyzed polycondensation of alkoxysilane monomers in liquid crystalline phases of nonionic CnEm surfactants. The liquid crystalline phase is retained when the monomers polymerize. The high molecular weight molecules formed phase separate from the mesophase and are subsequently organized by it to form micron-sized particles. A variety of particle morphologies are formed by organization of the polymer particles in the mesophase. For condensation of dimethyldimethoxysilane (DMS, with trimethoxysilane, TMS as crosslinker) in hexagonal and lamellar phases, specific reaction conditions, viz. slow condensation kinetics and low crosslink density, give rod-like particles in hexagonal phases and sheet-like structures in lamellar phases. However, when higher acid concentrations are used, the reaction kinetics accelerates and irregular particles form. Irregular particles also form when the fraction of trifunctional crosslinker is increased, and finally complex flower-like structures form for condensation of trimethoxysilane in the hexagonal phase. The particle morphology formed is crucially dependent on the details of the polycondensation rate, crosslinker density and surfactant-monomer/oligomer interactions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: nonionic; surfactant; templated synthesis

Reverse microemulsion mediated sol-gel synthesis of lithium silicate nanoparticles under ambient conditions: Scope for CO2 sequestration - Khomane, Ramdas B.; Sharma, B. K.; Saha, S.; Kulkarni, B. D. (Chemical Engineering Science, 2006)
We report on the synthesis of nanocrystalline lithium silicate by coupling of sol-gel method in reverse microemulsion. The sample calcined at 800 degrees C gives pure phase lithium metasilicate nanocrystallites. X-ray diffraction and transmission electron microscopy confirmed the formation of nanocrystalline lithium silicate particles with a narrow size distribution. The nanoparticle prepared in the microemulsion shows enhanced CO2 sorption capacity and shorter retention times at higher temperature (similar to 131 ml/g at STP at 610 degrees C which are better than the best known results. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; Carbon dioxide; Microemulsion; particle; separations; sol-gel; surfactant

Synthesis and characterization of novel organo-montmorillonites - Tiwari, Rajkiran R.; Khilar, Kartic C.; Natarajan, Upendra (Applied Clay Science, 2008)
Sodium Montmorillonite (NaMMT) has been modified via cation exchange reaction using three different organic cations. Basal spacings, interlamellar structure and thermal stability of these organo-montmorillonites (OMMT) clays have been characterized using wide angle X-ray diffraction (WARD) and thermogravimetric analysis (TGA) techniques. Increase in the basal spacing due to organic modification is in good agreement with simple theoretical calculations based on van der Waals volume of the cationic ammonium ions. TGA characterization and analysis show that the amount of organic modifier in the OMMT's is in good agreement with theoretically calculated stoichiometric content expected for almost complete exchange of Na+ ions by organic cations. The OMMT's shows stepwise decomposition corresponding to initial weight loss from residual water desorption, followed by decomposition of the organic surfactant and the dehydroxylation of structural water of the montmorillonite layers. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Montmorillonite; organo-clays; organo-montmorillonite; surfactant

Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Enhanced clathrate hydrate formation kinetics at near ambient temperatures and moderate pressures: Application to natural gas storage - Veluswamy, Hari Prakash; Kumar, Sharad; Kumar, Rajnish; Rangsunvigit, Pramoch; Linga, Praveen (Fuel, 2016)
SNG (solidified natural gas) technology via clathrate hydrates is a potential method for large scale stationary storage of natural gas. Clathrate hydrate formation kinetics in presence of methane and 5.6 mol% tetrahydrofuran (THF) was investigated in an unstirred reactor configuration at moderate pressure and temperature conditions. It is well known that the presence of THF generally improves the thermodynamic stability of the resulting hydrate. In order to study the scale-up potential of this approach, kinetics of hydrate growth at temperatures close to ambient conditions and moderate pressures is required. Hydrate formation experiments were performed at three different temperatures - 283.2 K, 288.2 K and 293.2 K and at experimental pressures of 7.2 MPa, 5.0 and 3.0 MPa. Further, we report a synergistic effect of kinetic promotion of mixed methane hydrate formation by coupling THF and sodium dodecyl sulfate (SDS) at 293.2 K. For the first time, we observe rapid mixed methane/THF hydrate formation kinetics at 293.2 K in presence of just 100 ppm sodium dodecyl sulfate surfactant with methane gas uptake of 3.45 (+/- 0.17) kmol/m(3) of water in 1 h. This is also the first study to demonstrate such rapid hydrate formation kinetics with significant methane storage capacity at temperature of 293.2 K (closer to the ambient temperature). Further, substantial methane gas uptake of 3.52 (+/- 0.13) kmol/m(3) of water is possible even at reduced experimental pressure of 3.0 MPa and 283.2 K in 2 h. Minimal energy requirement in an unstirred reactor for mixed methane/THF hydrate formation storage can propel the SNG technology for large scale commercial deployment. Further improvement in the process can be achieved by optimizing the cooling requirement through innovative reactor design and operating the process in a semi-batch or continuous mode. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Methane hydrates; Natural gas storage; Rapid kinetics; surfactant; Tetrahydrofuran; Unstirred reactor

Synthesis of copper nanoparticles in presence of surfactants and evaluation of heat transfer performance of copper nanofluid - Kapadnis, Chetan V.; Gundeli, Kartik P.; Saini, Daulat R.; Bhatkhande, Dhananjay S. (Journal of Nanofluids, 2017)
Copper nanoparticles were synthesized by reduction of copper nitrate hexahydrate using glucose as a green reducing agent. Effect of various synthesis parameters such as the amount of reducing agent, type of surfactant, the concentration of surfactant on particle size and morphology has been studied. Particles thus synthesized were characterized using analytical tools like X-ray Diffraction (XRD), Dynamic Light Scattering (DLS) and Scanning Electron Microscopy (SEM). XRD results show copper peaks at 2 angles 43.34, 50.48 and 74.19° corresponding to the planes (111), (200) and (220) respectively and possessing FCC (Face Centred Cubic) crystal lattice and polydispersed particles with crystallite size ranging from 43 to 103 nm. Further Cu nanoparticles were dispersed in water to prepare nanofluid and heat transfer properties such as heat transfer coefficient, viscosity and density were evaluated. Nanofluid models proposed elsewhere were also used for theoretical property evaluations. Nearly 100% increase in heat transfer coefficient was observed at 1% (by volume) particle concentration of copper nanoparticles in water.
Keywords: Chemical Reduction; Copper nanoparticles; green synthesis; Nanofluids; surfactant

Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template